Transcripts with high distal heritability mediate genetic effects on complex metabolic traits - Anna L. Tyler; J. Matthew Mahoney; Mark P. Keller; Candice N. Baker; Margaret Gaca; Anuj Srivastava; Isabela Gerdes Gyuricza; Madeleine J. Braun; Nadia A. Rosenthal; Alan D. Attie; Gary A. Churchill; Gregory W. Carter (Nature Communications)
Abstract Although many genes are subject to local regulation, recent evidence suggests that complex distal regulation may be more important in mediating phenotypic variability. To assess the role of distal gene regulation in complex traits, we combine multi-tissue transcriptomes with physiological outcomes to model diet-induced obesity and metabolic disease in a population of Diversity Outbred mice. Using a novel high-dimensional mediation analysis, we identify a composite transcriptome signature that summarizes genetic effects on gene expression and explains 30% of the variation across all metabolic traits. The signature is heritable, interpretable in biological terms, and predicts obesity status from gene expression in an independently derived mouse cohort and multiple human studies. Transcripts contributing most strongly to this composite mediator frequently have complex, distal regulation distributed throughout the genome. These results suggest that trait-relevant variation in transcription is largely distally regulated, but is nonetheless identifiable, interpretable, and translatable across species.